A pilot phase II study of ofatumumab monotherapy for extranodal marginal zone B‐cell lymphoma of the mucosa‐associated lymphoid tissue (MALT) lymphoma. Issue 1 (10th July 2017) - Kiesewetter, Barbara; Neuper, Ortrun; Mayerhoefer, Marius E.; Dolak, Werner; Lukas, Julius; Simonitsch‐Klupp, Ingrid; Raderer, Markus
Abstract: These are the final results of the Ofatumumab in MALT lymphoma study (O‐MA 1), a pilot phase II trial evaluating the capacity and safety of ofatumumab to induce objective responses in patients with Helicobacter pylori eradication refractory or extragastric MALT lymphoma. Ofatumumab was given at 4 weekly doses (1000 mg) followed by 4 doses at 2‐month intervals starting at week 8. According to protocol, a total of 16 patients were recruited (median age 69 years; range 38‐85). Thirty one percent (5/16) of patients had primary gastric MALT lymphoma while the remaining 69% (11/16) presented with extragastric manifestations. Seventy‐five percent (12/16) had localized lymphoma and 4 patients disseminated disease. The overall response rate to treatment with ofatumumab was 81% (13/16), with the median time to best response being 5.5 months. In detail, 50% (8/16) achieved complete remission; 31% (5/16), partial remission; and 19% (3/16), disease stabilization as best response. However, 1 patient with gastric lymphoma and complete remission at second restaging had a relapse at final assessment but ongoing complete remission during further follow‐up. Tolerability was excellent accept low‐grade infusion reactions occurring in 86% (14/16). At a median follow‐up time of 25 months only 1 patient has relapsed suggesting durable responses in the majority of patients. This pilot trial shows clearly that ofatumumab is active and safe for the treatment of MALT lymphoma.